(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
A performance appraisal (PA) is a structured and periodic process that measures the performance and efficiency of individual employees in relation to clearly specified organizational requirements and objectives. Many aspects of each employee such as attitude, achievements, future growth potential, strengths and weaknesses, etc. are also considered. The main reason why performance appraisals (PAs) are used is to improve results (initially in the workforce and eventually in the organization). Many fundamental reasons include, as a basis for employment decisions (e.g. promotion, termination, transfers), as testing criteria (e.g. validating tests), to facilitate interactions (e.g. encouraging employees to know how and organizational expectations) to develop personal training goals programmes. Furthermore, PAs can help in developing work requirements and in selecting people who are ideally qualified to carry out the organizational tasks needed. A PA will help guide and track the growth of employee careers. The CA can also be used as part of the performance management plan to empower the workforce through incentive schemes career growth. One of the key reasons for an successful performance management plan is also one of the most overlooked. Far too often, the boss wrongly focuses far his or her attention on evaluating and classifying the workers, dolling promotions or laying off the employees as appropriate. Although these steps are an integral part of performance improvement, they are not long-term. Second, the workers feel abandoned as if their individual job needs have been ignored. This eventually leads to higher employee compensation and makes retaining top quality talent challenging for a company.